Telaah Kewirausahaan dalam Perspektif Islam - Sedya Santosa; Abdul Hafiz Alfatoni (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Muslims are also required to always be creative and develop the abilities that he has both in the world of education, the world of need and others. The research method used is library research is research conducted by collecting data from books that are used as data sources. In obtaining data the author took data from a book of articles related to Entrepreneurship in Islam. In Islam it is highly recommended to try and develop themselves from the potential that he has to be able to fulfill his ability well as explained in the Qur'an Surah Al-Jumuah verse 10 and Al-Al mujadalah verse 11. In this case, humans are required to seek knowledge and strive to develop themselves.